Impact of age on safety of Busulfan-Melphalan followed by autologous hematopoietic stem-cell transplantation versus standard chemotherapy in the patients of the EURO-E.W.I.N.G. 99 and Ewing 2008 clinical trials - Choderlos de Laclos, Xavier; Risbourg, Séverine; Marec-Bérard, Perrine; Cécile Le Deley, Marie; Tabone, Marie Dominique; Bertucci, François; Gaspar, Nathalie; Gandemer, Virginie; Brennan, Bernadette; Strauss, Sandra; McCabe, Martin G.; Windsor, Rachael; et al. (European Journal of Cancer, 2024)
Introduction: Ewing sarcoma (ES), is a rare cancer affecting children, adolescents and adults. After VIDE (vincristine-ifosfamide-doxorobucin-etoposide) induction chemotherapy, Busulfan-Melphalan (BuMel) high-dose chemotherapy followed by autologous hematopoietic stem cells transplantation improved outcomes in unfavourable localized ES, but with more toxicities than conventional chemotherapy (VAI: Vincristine-dactinomycin-Ifosfamide). We evaluated whether the risk of acute toxicity associated with BuMel compared to VAI varied according to age in patients recruited in the R2Loc and R2Pulm randomised trials of the Euro-E.W.I.N.G.99 and Ewing-2008 trials. Methods: We included patients with a localized high-risk disease, or pulmonary or pleural metastasis. We analysed the risk of severe toxicity according to randomised treatment group (VAI versus BuMel) and age group (<12 years, 12–17 years, 18–24 years, ≥25 years). We evaluated the heterogeneity of treatment effects by age group using interaction terms in logistic multivariable models. Results: The analysis included 243 patients treated with VAI and 205 with BuMel. Overall, BuMel was associated with a higher risk of severe acute toxicity than VAI particularly haematological, gastrointestinal, liver, sinusoidal occlusive syndrome, and infections. Severe haematological toxicity and lower general condition were significantly more frequent in younger patients, whatever treatment. We did not observe any significant heterogeneity in terms of the excess risk of severe toxicities associated with BuMel compared to VAI according to age group. Conclusion: The excess of acute toxicity associated with BuMel compared to VAI does not vary significantly with age, suggesting the feasibility of BuMel across all age groups.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Autologous hematopoietic stem cells transplantation; Ewing sarcoma (ES); High dose chemotherapy; Safety